PENGEMBANGAN MODEL PEMBELAJRAN PJOK TEMATIK TERINTEGRATIF TEMA DIRIKU (SUBTEMA 3: AKU MERAWAT TUBUHKU) UNTUK PESERTA DIDIK KELAS 1 SD DI KECAMATAN BULELENG - Mahaditya, Ida Bagus Gede Indra; Parwata, I Gusti Lanang Agung; Dartini, Ni Putu Dwi Sucita (Universitas Pendidikan Ganesha, 2021)
This study aims, 1) to develop an integrated thematic-based PJOK learning module with the theme myself sub-theme 3: I take care of my body for 1st-grade elementary school students in Buleleng District. 2) knowing the results of the expert validity test on the integrated thematic PJOK game module, sub-theme 3: I take care of my body for 1st-grade elementary school students in Buleleng District. This type of research is research on the development of R&D methods using the Borg and Gall design. The data collection instrument used was a questionnaire. The data analysis technique used is descriptive quantitative and qualitative. The results of the study show that 1) the design of the learning module uses three stages, namely: research and information gathering, planning, and developing a preliminary form of the product. These three stages resulted in an integrated thematic PJOK game module, sub-theme 3: I take care of my body for 1st-grade elementary school students. 2) validation of teaching materials in terms of content aspects with a total percentage of 91.76% being in the very good category. The media aspect with a percentage of 90% is in the very good category. The aspect of field practitioners with a percentage of 85% is in a good category. Based on the results of the study, it can be concluded that the development of an integrated thematic PJOK learning module with the theme of myself sub-theme 3: I take care of my body for 1st-grade elementary school students in Buleleng District is feasible to use.